2019
DOI: 10.1111/jfpe.13231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultra‐high pressure on the biochemical properties and secondary structure of myofibrillar protein from Oratosquilla oratoria muscle

Abstract: Oratosquilla oratoria (O. oratoria) were treated with 300, 350, and 400 MPa for 5, 8, and 10 min, respectively. The myofibrillar protein (MP) content, sulfhydryl content, Ca2+‐ATPase activity, surface hydrophobicity and secondary structure of MP were determined to investigate the effects of ultra‐high pressure (UHP) on the biochemical properties and secondary structure of MP from O. oratoria muscle. Results showed that the relatively low pressures have no significant effects on the MP content. When the pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…At the same time, in addition to the influence of heat, the influence of pressure changes on proteins cannot be ignored. The increase in pressure made the β ‐sheet continuously increase and the α ‐helix decrease ( P < 0.05), which was consistent with the research by Li et al 15 . An increase in pressure caused the hydrogen bond to change, and part of the α ‐helix was thus opened, resulting in a decrease in the content 15 .…”
Section: Resultssupporting
confidence: 88%
“…At the same time, in addition to the influence of heat, the influence of pressure changes on proteins cannot be ignored. The increase in pressure made the β ‐sheet continuously increase and the α ‐helix decrease ( P < 0.05), which was consistent with the research by Li et al 15 . An increase in pressure caused the hydrogen bond to change, and part of the α ‐helix was thus opened, resulting in a decrease in the content 15 .…”
Section: Resultssupporting
confidence: 88%
“…The impact of all the treatments on the β-turn content was not signi cant (p > 0.05). The destruction of the α-helix was due to the hydrogen bond change, whereas the signi cant increase in β-sheet content (p < 0.05) and a decrease in random coil might be due to the decrease in particle size (Gaoshang et al 2019). Similar results have been reported that UHP treatment reduced the αhelix content in myo brillar protein from Oratosquilla oratoria muscle (Gaoshang et al 2019) and increased β-sheet content in the myo brillar protein from Trichiurus Haumela Surimi (Chen et al 2020b).…”
Section: Ft-ir Analysesmentioning
confidence: 94%
“…The destruction of the α-helix was due to the hydrogen bond change, whereas the signi cant increase in β-sheet content (p < 0.05) and a decrease in random coil might be due to the decrease in particle size (Gaoshang et al 2019). Similar results have been reported that UHP treatment reduced the αhelix content in myo brillar protein from Oratosquilla oratoria muscle (Gaoshang et al 2019) and increased β-sheet content in the myo brillar protein from Trichiurus Haumela Surimi (Chen et al 2020b). Shi et al ( 2019) have found the β-turn proportion in the clam shell myo brillar was decreased after HPH treatment, which was inconsistent with our results.…”
Section: Ft-ir Analysesmentioning
confidence: 94%
See 1 more Smart Citation
“…The amide I region (1,700-1,600 cm −1 ) produced by C = O expansion vibration exhibits a wider peak , and the maximum absorption wavelength was at ~1,656 cm −1 . The amide I band, as the most sensitive indicator of protein secondary structural composition (Kong & Yu, 2007), is a complex mixture of several overlapping protein structural forms (Barth, 2007), where regions 1,640-1,600, 1,650-1,641, 1,660-1,651 and 1,700-1,661 cm −1 represent the β-sheet, random coil, α-helix, and β-turn conformation respectively (Gaoshang et al, 2019). Multi-peak fitting with Gaussian functions was applied using PeakFit 4.11 to quantify the multicomponent peaks in the amide I band (Figure S1).…”
Section: Determination Of the Change Of Protein Secondary Structure And Characteristic Peaks Of Oilmentioning
confidence: 99%